Effect of Pentavac and measles-mumps-rubella (MMR) vaccination on the intestine. Issue 6 (1st December 2002) - Thjodleifsson, B; Davídsdóttir, K; Agnarsson, U; Sigthórsson, G; Kjeld, M; Bjarnason, I
Abstract : Background: The safety of infant vaccination has been questioned in recent years. In particular it has been suggested that the measles, mumps, and rubella (MMR) vaccination leads to brain damage manifesting as autism consequent to the development of an "enterocolitis" in the immediate post-vaccination period. Aim: To assess if MMR vaccination is associated with subclinical intestinal inflammation, which is central to the autistic "enterocolitis" theory. Methods: We studied 109/58 infants, before and two and four weeks after immunisation with Pentavac and MMR vaccines, for the presence of intestinal inflammation (faecal calprotectin). Results: Neither vaccination was associated with any significant increase in faecal calprotectin concentrations. Conclusions: The failure of the MMR vaccination to cause an intestinal inflammatory response provides evidence against the proposed gut-brain interaction that is central to the autistic "enterocolitis" hypothesis.